Recurrent stroke and patent foramen ovale: a systematic review and meta-analysis - Katsanos, Aristeidis H; Spence, J David; Bogiatzi, Chrysi; Parissis, John; Giannopoulos, Sotirios; Frogoudaki, Alexandra; Safouris, Apostolos; Voumvourakis, Konstantinos; Tsivgoulis, Georgios (Stroke, 2014)
BACKGROUND AND PURPOSE: Recurrent cerebrovascular events are frequent in medically treated patients with patent foramen ovale (PFO), but it still remains unclear whether PFO is a causal or an incidental finding. Further uncertainty exists on whether the size of functional shunting could represent a potential risk factor. The aim of the present study was to evaluate if the presence of PFO is associated with an increased risk of recurrent stroke or transient ischemic attack and to investigate further if this relationship is related to the shunt size. METHODS: We conducted a systematic review and meta-analysis according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines of all available prospective studies reporting recurrent cerebrovascular events defined as cryptogenic stroke and transient ischemic attacks in medically treated patients with PFO diagnosed by echocardiography or transcranial sonography. RESULTS: We identified 14 eligible studies including a total of 4251 patients. Patients with stroke with PFO did not have a higher risk of the combined outcome of recurrent stroke/transient ischemic attack (risk ratio=1.18; 95% confidence interval=0.78-1.79; P=0.43) or in the incidence of recurrent strokes (risk ratio =0.85; 95% confidence interval=0.59-1.22; P=0.37) in comparison with stroke patients without PFO. In addition, PFO size was not associated with the risk of recurrent stroke or transient ischemic attack. We also documented no evidence of heterogeneity across the included studies. CONCLUSIONS: Our findings indicate that medically treated patients with PFO do not have a higher risk for recurrent cryptogenic cerebrovascular events, compared with those without PFO. No relation between the degree of PFO and the risk of future cerebrovascular events was identified.
Keywords: recidiva; transesophageal echocardiography; Recurrence; rizikové faktory; cévní mozková příhoda; transcranial Doppler ultrasonography; Humans; foramen ovale apertum; lidé; prospektivní studie; Risk Factors; ischemic attack, transient; foramen ovale, patent; stroke; Stroke; Foramen Ovale, Patent; Prospective Studies